F2R-CWANA Egypt and Sudan Inception Workshop - Baum, Michael; Al-Zu'bi, Maha; Crichton, Rhiannon (International Center for Agricultural Research in the Dry Areas, 2023)
F2R-CWANA Egypt and Sudan Inception Workshop